2022
DOI: 10.48550/arxiv.2207.12926
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Guide to Image and Video based Small Object Detection using Deep Learning : Case Study of Maritime Surveillance

Abstract: Small object detection (SOD) in optical images and videos is a challenging problem that even state-of-the-art generic object detection methods fail to accurately localize and identify such objects. Typically, small objects appear in real-world due to large camera-object distance. Because small objects occupy only a small area in the input image (e.g., less than 10%), the information extracted from such a small area is not always rich enough to support decision making. Multidisciplinary strategies are being dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 256 publications
0
10
0
Order By: Relevance
“…One of these areas pertains to the real-time detection of small vessels, individuals, and other objects in maritime environments using aerial images obtained from drones or small aircraft. Developing robust and precise models for this application would prove to be highly beneficial in search and rescue missions, humanitarian aid efforts, and surveillance [ 2 , 3 , 4 ] and security operations. However, as we have previously noted in our publication [ 5 ], the primary issue is the high cost of capturing such images and the fact that instances in these images tend to be very small.…”
Section: Introductionmentioning
confidence: 99%
“…One of these areas pertains to the real-time detection of small vessels, individuals, and other objects in maritime environments using aerial images obtained from drones or small aircraft. Developing robust and precise models for this application would prove to be highly beneficial in search and rescue missions, humanitarian aid efforts, and surveillance [ 2 , 3 , 4 ] and security operations. However, as we have previously noted in our publication [ 5 ], the primary issue is the high cost of capturing such images and the fact that instances in these images tend to be very small.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we surveyed numerous strategies employed in deep learning to enhance the performance of small object detection in optical images and videos up to the year 2022 [11]. We showed that beyond the adaptation of newer deep learning structures such as transformers, prevalent approaches include data augmentation, super-resolution, multi-scale feature learning, context learning, attention-based learning, region proposal, loss function regularization, leveraging auxiliary tasks, and spatiotemporal feature aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we observed that transformers are among the leading methods in localizing small objects across most datasets. However, given that [11] predominantly evaluated over 160 papers focusing on CNN-based networks, an in-depth exploration of transformer-centric methods was not undertaken. Recognizing the growth and exploration pace in the field, there is a timely window now to delve into the current transformer models geared towards small object detection.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations